Β-blocker therapy and heart rate control during exercise testing in the general population: role of a common G-protein β-3 subunit variant. (September 2010) - Dörr, Marcus; Schmidt, Carsten O; Spielhagen, Thomas; Bornhorst, Alexa; Hentschel, Katharina; Franz, Christina; Empen, Klaus; Kocher, Thomas; Diehl, Scott R; Kroemer, Heyo K; Völzke, Henry; Ewert, Ralf; et al.
Aim: Impaired heart rate (HR) response to exercise is associated with increased cardiovascular morbidity and mortality. We analyzed whether common variants (rs5443/C825T and rs5442/G814A) in the G-protein β3 subunit ( GNB3 ) gene modulate interindividual variation in β-blocker responses with respect to HR.Materials & methods: Among 1614 subjects (347 current β-blocker users) of a population-based study, HR during symptom-limited exercise testing was analyzed by multilevel linear regression models adjusted for potential confounders.Results: In β-blocker users, but not in nonusers, HR was attenuated in rs5443 T allele carriers (TC/TT vs CC) with lower adjusted HR over the entire exercise period from rest to peak workload (3.5 bpm; 95% CI: 1.1–5.8; p < 0.01), and during recovery (4.2 bpm; 95% CI: 0.6–7.8; p = 0.02). The genotype-related HR reducing effect at peak exercise varied by up to 7.5 bpm (CC vs TT), more than a third (35.9%) of the total β-blocker effect (20.9 bpm). By contrast, rs5442 had no impact on any HR-related parameter.Conclusion: In this population-based sample, a common GNB3 polymorphism (C825T) was significantly related with response to β-blocker therapy with respect to HR during exercise and HR recovery, respectively. Further prospective studies are needed to confirm these associations and to examine their potential clinical relevance.